Cardioprotective approaches when prescribing iSGLT-2 - Mukhtarova, SHakhnoza; Trigulova, Raisa; Nasirova , Khurshida (CARDIOLOGY OF UZBEKISTAN, 2024)
Background. Sodium-Glucose Cotransporter-2 (NGLT-2) inhibitors have gained significant attention for their cardioprotective properties. This review explores the cardiovascular benefits of NGLT-2 inhibitors, particularly their impact on heart health in patients with comorbidities such as type 2 diabetes and heart failure. The primary objective is to evaluate the mechanisms and effectiveness of these inhibitors in improving cardiovascular outcomes.Methods. A comprehensive review of relevant literature was conducted, focusing on recent studies, including clinical trials and meta-analyses, to assess the impact of NGLT-2 inhibitors on heart failure, diabetes, and associated cardiovascular events. The review examines various approaches related to the use of NGLT-2 inhibitors in treating cardiovascular conditions.Key Content and Findings. NGLT-2 inhibitors have been shown to significantly reduce the risk of cardiovascular events, including heart failure hospitalizations and mortality. Their mechanisms of action include improving glucose control, reducing kidney burden, and mitigating endothelial dysfunction. The review highlights these mechanisms and the clinical benefits in treating patients with heart failure and type 2 diabetes.Conclusion. NGLT-2 inhibitors represent a valuable treatment option for improving heart health in patients with type 2 diabetes and heart failure. Further research is needed to optimize their use and fully understand their underlying mechanisms.